Aplikasi Monitoring Proses Distribusi Makanan Beku Untuk Informasi Secara Realtime - Susliansyah, Susliansyah; Handayanna, Frisma (STIKOM Tunas Bangsa Pematangsiantar, 2018)
The control of frozen food distribution process done by the logistic part in obtaining the data is still manual, using the form and excel, causing the admin difficulty in monitoring and controlling the distribution process or the delivery of frozen food to store or outlet. Problem solving is made an application using data collection method and RAD method, where the model of Rapid Application Development (RAD) has business modeling stage using kebutuah application admin and user, data modeling that explains the use of ERD and LRS from the database side, about usecase diagrams and activity diagrams from the application process side, application generation evolves about programming languages in application creation while testing and turnover describes the use of white box testing. The purpose of the application is made to facilitate the related division in processing the data distribution process, monitor and control the distribution process and obtain information distribution process in realtime.